2012
DOI: 10.1111/j.1365-2702.2012.04163.x
|View full text |Cite
|
Sign up to set email alerts
|

The locus of pain control in patients with lower limb ulcerations

Abstract: The control of pain in ulceration patients is mostly determined by the support of medical personnel, which generally should be considered a negative finding. Relevance to clinical practice.  Determination of the locus of pain control should be included in the complex medical evaluation of individuals suffering from ulcerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…However, significant intergroup differences pertained to annoyance of physical symptoms – this was significantly higher in patients with ulcerations of arterial and mixed etiology. This finding is consistent with literature data; many authors observed that the etiology of the ulceration is the main clinical determinant of physical discomfort experienced by the patient [ 10 , 11 , 13 , 16 , 31 – 34 ]. Additionally, the lack of significant intergroup differences in global quality of life and its various components suggests that patients with ulcerations of arterial and mixed etiology do not transfer unfavorable physical sensations associated with the disease onto other spheres of their quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…However, significant intergroup differences pertained to annoyance of physical symptoms – this was significantly higher in patients with ulcerations of arterial and mixed etiology. This finding is consistent with literature data; many authors observed that the etiology of the ulceration is the main clinical determinant of physical discomfort experienced by the patient [ 10 , 11 , 13 , 16 , 31 – 34 ]. Additionally, the lack of significant intergroup differences in global quality of life and its various components suggests that patients with ulcerations of arterial and mixed etiology do not transfer unfavorable physical sensations associated with the disease onto other spheres of their quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…The experience of living daily in pain was a meaning often attributed to people with chronic wounds 7,[21][22][23][27][28][29][30][31][32][33][34][35] . Previous studies 32,[36][37][38] showed that the pain symptom is the most commonly reported by the interviewees, followed by secretions, odors, discomfort, anxiety and depression, which is in accordance with the findings of this meta-synthesis.…”
Section: Initial Concerns and Appearance Of Symptomssupporting
confidence: 92%
“…According to the study by Wiśniewska et al,10 the intensity of pain in patients with peripheral arterial disease (PAD) is high and patients are convinced about the influence of the external factors in pain control. Similarly in the case of the patients studied by Cwajda-Białasik et al,11 external factors intensified pain ailments. In the case of rheumatoid arthritis (RA), in turn, according to the study by Jia and Jackson,12 belief about internal control with the simultaneous reduction of external control influenced the reduction of pain ailments, in the sense of helplessness and of anxiety.…”
Section: Introductionmentioning
confidence: 58%
“…Simultaneously, along with the increase of pain intensity, belief about the influence of medical care on pain control decreased and belief about internal control increased 10. Another study revealed that patients with chronic constant ischemic pain of the lower extremities more frequently passively succumbed to the disease, they manifested the locus of pain control mainly in external factors and associated relief in suffering with the help of the medical staff and the therapy proposed by that staff 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation